PEMAHAMAN AL-QURAN HADIS TENTANG MENJAUHI PERGAULAN BEBAS DAN KORELASINYA TERHADAP SIKAP JALINAN ASMARA - Moh. Misbakhul Khoir Misbah; zainal Hakim; Ismail Abdullah (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2022)
Cases of sexuality due to promiscuity have become a serious problem among teenagers. One of the important efforts in overcoming this is increasing religious understanding, especially the understanding of the Qur'an and Hadith. In theory, it is stated that religiosity is able to produce commendable human character. This study tries to prove this theory, with a focus on finding a correlation between the understanding of the Koran and Hadith about the prohibition of promiscuity with students' romantic relationships. The research method applied is quantitative research with the main data source being students of class XI MAN 1 Mojokerto Regency. In measuring the understanding of the Qur'an and Hadith, a test instrument is used. Meanwhile, in measuring the attitude of the love affair, a questionnaire instrument was used. The data from the two variables were then measured for their correlation. The results of the study stated that there was a correlation between the variables of understanding the Qur'an and Hadith (X) and the attitude of romance (Y). The correlation between the variables X and Y is significant (significant) and positive, but in the low category. So it can be concluded that the relationship attitude 30% is influenced by the understanding of the Qur'an and Hadith, the remaining 70% is influenced by other factors beyond understanding. This conclusion is in line with the theory developed previously.